Mitochondrial H2O2 Is a Central Mediator of Diclofenac-Induced Hepatocellular Injury - Sin Ri Kim; Ji Won Park; You-Jin Choi; Seong Keun Sonn; Goo Taeg Oh; Byung-Hoon Lee; Tong-Shin Chang (MDPI AG, 2023)
Nonsteroidal anti-inflammatory drug (NSAID) use is associated with adverse consequences, including hepatic injury. The detrimental hepatotoxicity of diclofenac, a widely used NSAID, is primarily connected to oxidative damage in mitochondria, which are the primary source of reactive oxygen species (ROS). The primary ROS responsible for inducing diclofenac-related hepatocellular toxicity and the principal antioxidant that mitigates these ROS remain unknown. Peroxiredoxin III (PrxIII) is the most abundant and potent H2O2-eliminating enzyme in the mitochondria of mammalian cells. Here, we investigated the role of mitochondrial H2O2 and the protective function of PrxIII in diclofenac-induced mitochondrial dysfunction and apoptosis in hepatocytes. Mitochondrial H2O2 levels were differentiated from other types of ROS using a fluorescent H2O2 indicator. Upon diclofenac treatment, PrxIII-knockdown HepG2 human hepatoma cells showed higher levels of mitochondrial H2O2 than PrxIII-expressing controls. PrxIII-depleted cells exhibited higher mitochondrial dysfunction as measured by a lower oxygen consumption rate, loss of mitochondrial membrane potential, cardiolipin oxidation, and caspase activation, and were more sensitive to apoptosis. Ectopic expression of mitochondrially targeted catalase in PrxIII-knockdown HepG2 cells or in primary hepatocytes derived from PrxIII-knockout mice suppressed the diclofenac-induced accumulation of mitochondrial H2O2 and decreased apoptosis. Thus, we demonstrated that mitochondrial H2O2 is a key mediator of diclofenac-induced hepatocellular damage driven by mitochondrial dysfunction and apoptosis. We showed that PrxIII loss results in the critical accumulation of mitochondrial H2O2 and increases the harmful effects of diclofenac. PrxIII or other antioxidants targeting mitochondrial H2O2 could be explored as potential therapeutic agents to protect against the hepatotoxicity associated with NSAID use.